Finding etiological factors for the onset of neonatal sepsis diagnosed in tertiary care hospitals in Dhaka, Bangladesh - Dayem, Shabnoor Binte (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfilment of the requirements for the degree of MS in Biotechnology, 2024.